Impact of Combined Application of Incineration Ash of Sugar Factory and Farmyard Manure on Rice Yield, Soil Properties and Nutrient Balance - Veena J. (Journal of the Indian Society of Soil Science, 2023)
A field experiment was conducted in a sandy clay soil at Maddur taluk, Mandya District to study the effect of incineration ash on the properties of rice soil during kharif 2017. The study comprised of seven different combinations of fertilizer, ash, and farmyard manure (FYM). The results of the study revealed that application of recommended dose of fertilizers (RDF) along with 10 t ha-1 of FYM and 10 t ha-1 of incineration ash recorded significantly higher grain and straw yields (9.06 and 10.15 t ha-1, respectively). It is possible that the higher rice yield is related to the balanced application of nutrients via RDF and FYM. Furthermore, incineration ash contains more potassium (K), which may have aided in the translocation and accumulation of nutrients, as well as the provision of secondary nutrients. Available nutrient contents in soil at rice harvest were K2O 371 kg ha-1, Na 1.74 cmol(p+)kg-1, Ca 13.5 cmol(p+)kg-1, Mg 5.47 cmol(p+)kg-1, S 21.2 mg kg-1, Fe 16.8 mg kg-1, Mn 6.92 mg kg-1, Cu 1.83 mg kg-1 and B 0.93 mg kg-1. The higher K concentration in the ash is responsible for the higher accessible K content in the soil. However, differences in soil pH, electrical conductivity, organic carbon and Zn contents were found to be statistically non-significant due to submergence. The application of higher levels of incinerator ash and FYM resulted in a positive balance of soil N.